Pendampingan Pendalaman Materi Matematika Berbasis Etnomatematika Santri Pondok Pesantren Cijantung 7 Kalabahi - Likur, Fadhillah Abdul Halik; R, Nurdin; Balikh, Ratna Abdul Pakdin; Sibala, Ismawati; Peka, Musrifa (Universitas Negeri Gorontalo, 2025)
One thing that can bridge the gap between culture and education is ethnomathematics. Ethnomathematics is a form of mathematics influenced by or based on culture. Through the application of ethnomathematics in education, especially mathematics education, will bring better understanding of students about both knowledge and culture of theirs. This way will help teacher for teaching cultural values in students so that cultural values which are part of the national character are embedded from an early age of student. The formation of this new scheme should be from the scheme that already exists in the student. Therefore, in teaching formal mathematics (school mathematics), teachers should start with informal mathematics which is applied by children in society. If a child has a good schema about mathematics used in daily basis increase the existing knowledge the teacher strengthens the existing schema or forms a new schema based on the existing schema.